Respon Pertumbuhan Semai Tancang (Bruguiera gymnorrhiza (L.) Lamk.) Terhadap Tingkat Penggenangan di Kawasan Mangrove Jalan Tol Sedyatmo, Jakarta Utara - Indah Permatasari; Cecep Kusmana (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2011)
The Growth Responses of Tancang (Bruguiera gymnorrhiza (L.) Lamk.) Seedlings on Inundation Level in Mangrove Area of Sedyatmo Highway, North JakartaIndonesia as a mega biodiversity country has the mangrove forests, mainly growing in the protected coastal areas. In relation to the global warming, those mangroves are threatened by the raising of sea level. So that, the information about the response of mangroves to the inundation should be explored. This study is aimed to elaborate the growth response of mangrove seedlings of Bruguiera gymnorrhiza to the degree of inundation and to determine the degree of inundation which gives the best effect to the growth of seedlings. This research used Randomized Complete Block Design with inundation level as the treatment which is divided into three treatment stages, that are inundation until limit of the root neck, inundation between ¼ seedling height and ½ seedling height, and inundation between ½ seedling height and ¾ seedling height. Mangrove species that is used in this research is six months years old seedling of tancang (Bruguiera gymnorrhiza (L.) Lamk.). The research results showed that inundation level which gave the best effect to the growth of B. gymnorrhiza seedling is inundatoion until limit of the root neck. However, B. gymnorrhiza can adapt and having good growth at the inundation up to ½ seedling height.